Smartphone-Based Interactive Media Improves Communication Skills in Vocational School Students - Roemintoyo; Mochamad Kamil Budiarto (Jurnal Pendidikan dan Pengajaran, 2025)
Rapid technological advances pose challenges in integrating it effectively into teaching, especially in using digital learning materials through interactive media formats that can be accessed via smartphones. This problem is urgent because of the need to improve the communication skills of Vocational High School (SMK) students, which is very important to prepare them to face the demands of the modern world of work. This research aims to develop and evaluate smartphone-based interactive media to improve vocational school students' communication skills. The Research and Development (R&D) method is used with the Alessi and Trollip model, which includes three main stages: planning, design, and development. The subjects of this research involved media experts, subject matter experts, teacher practitioners, and vocational school students. Data collection instruments include observation, interviews, and questionnaires, with descriptive data analysis used to evaluate the feasibility and effectiveness of the media through pretest and posttest. The research results show that smartphone-based interactive media is very effective in improving students' communication skills, as evidenced by the high scores obtained in the N-Gain category. Using smartphone-based interactive media can significantly increase learning effectiveness in vocational schools. Therefore, it is recommended that these media be applied to other subjects to improve students' 21st-century competencies and better prepare them to compete in an increasingly complex and dynamic world of work. This research has significant implications for vocational education practice in the digital era. By utilizing technology familiar to students, such as smartphones, the learning process becomes more interesting and relevant, increasing students' motivation and active participation in learning activities.